Modification of calcium in the menopause - Paredes Pérez, Napoleón (2015)
Menopause in women means the end of the fertile part of life and marks the beginning of a postreproductora phase under the conditions of contemporary industrialized society, it can reach about a third of all life. This phenomenon that occurs during menopause, it is preceded by several years of declining fertility and irregular menstrual cycles and many women is accompanied by physical and psychological discomfort of varying intensity. The proportion of menopausal and postmenopausal women in some contemporary populations have become so large that it is necessary to decide whether, from a biological point of view is a special population.